The Effect Of Work Ethos, Work Ethics, And Employee Loyalty On Employee Productivity The Sofa Industry In Tarub District, Tegal Regency - Maulana agil Sumawang; Sri Murdiati; Yuniarti Herwinarni (LP2M IAIN Palopo, 2026)
Employees play a crucial role in the production process and the sustainability of a business; employee productivity generates output in the form of goods and services. High-quality human resources lead to increased employee productivity, and vice versa. The purpose of this study is to analyze the decline in employee productivity in the sofa industry in Tarub Subdistrict, Tegal Regency, Central Java, and the factors influencing it. Methods: This is a quantitative study using numerical data. The sampling technique employed was random sampling. The population and sample consisted of 77 employees in the sofa industry in Tarub Subdistrict, Tegal Regency. Primary data were obtained through interviews with respondents and a questionnaire technique, which involved providing respondents with a set of written statements to be answered using a Likert scale. The collected primary data were tested for validity and reliability of the research instrument using SPSS 25. This was followed by data processing and analysis, including assumption testing (covering normality, heteroscedasticity, and multicollinearity tests) and multiple linear regression analysis. Finally, hypothesis testing was conducted to obtain t-test results, F-test results, and the coefficient of determination. Results: The t-test for the Work Ethic variable shows a positive effect on Employee Productivity (3.395 > 1.666 and p-value 0.000 ≤ 0.05), meaning Hypothesis 1 is “accepted.”; The Work Ethic variable has a positive effect on Employee Productivity (12.300 > 1.666 and p-value 0.000 ≤ 0.05), meaning Hypothesis 2 is “accepted.” The Employee Loyalty variable has a positive effect on Employee Productivity (4.373 > 1.666 and p-value 0.000 ≤ 0.05), meaning Hypothesis 3 is “accepted”. All three variables have a simultaneous effect on Employee Productivity (62.113 > 2.730 and sig. 0.000 ≤ 0.05), meaning Hypothesis 4 is “accepted,” supported by the coefficient of determination indicating that the three variables contribute 70.7% to employee productivity.